Ground-penetrating radar surveys and ice volume estimates of Wedel Jarlsberg Land glaciers, Svalbard - Navarro Valero, Francisco José; Martín Español, Alba; Otero García, Jaime; Lapazaran Izargain, Javier Jesús; Vasilenko, Evgeniy; Grabiec, M. (E.T.S.I. Telecomunicación (UPM), 2013)
We present volume calculations, with detailed error estimates, for eight glaciers on Wedel Jarlsberg Land, southern Spitsbergen, Svalbard, and compare them to those obtained from area-volume scaling relationships. The volume estimates are based upon a dense net of GPR-retrieved ice thickness data collected over several field campaigns spanning the period 2004-2011.